Engagement in research during specialist geriatric medicine training: results of a national trainee survey. Issue 6 (2022) - Lim, Stephen; Cox, Natalie; Hale, Matthew; White, Lauren; Welch, Carly; Lochlainn, Mary Ní; Burton, Jennifer K; Richardson, Sarah J; Walesby, Katherine; Willott, Ruth; Makin, J Stephen; Taylor, Joanne
No abstract available